The Role of Cities in the Socio-Ecological Transition of Europe (ROCSET) - Thomas Sauer; Stephanie Barnebeck; Yannick Kalff; Judith Schicklinski; Susanne Elsen; Cristina Garzillo; Johanna Hopp; Stefan Kuhn (WWWforEurope, 2015)
Taking into account the potentially different starting and framework conditions of cities in different regions of the European Union, we present a new approach for sustainability transition analysis with a special focus on the governance of urban common-pool resources. The aim is to identify the conditions which are supportive for innovative institutional arrangements, like self-organised and co-operative forms of governance for urban resource systems like energy, water and green spaces. This report explores these conditions systematically focussing on the overarching research question: What is the transformative role of institutional diversification and innovation in the governance of core urban common pool resources? The role of the resource systems energy, urban green spaces and drinking water is empirically analysed in field studies of 40 European cities, exploring the potential for local self-organisation and socio-ecological transition.
Keywords: Q56; R11; D70; 330; Beyond GDP; Biophysical constraints; Common-pool resources; Energy; Green spaces; Water; Multi-level governance; Urban commons; Socio-ecological transition; Sustainable cities; Sustainable urban transitioning